Lexical and Morphological Analyses of Zuhair ibn Abi Sulma's Wisdom Poem in The Curriculum of the Twelfth High School Grade in The Kurdistan Region of Iraq, With A Methodological Perspective. (Raparin Journal of Humanities (RJH), 2025)
This research is a linguistic analysis of a poem called " Al- Hikmiyya" by a poet named (Zuhair Ibn Abi Salma),which is included in the high school curriculum for the 12th grade in the Kurdistan region of Iraq. It provides a systematic technique through an analysis of the poem, with the aim to display how such linguistic forms affect the meanings that the poem conveys, and how these forms assist in donating to convey ethical and social meanings with these encompassing teachings on human behavior. The school textbook has such impressively crucial and central role in raising and educationally shaping generations.Therefore, its composition and its production in form and content based on educational, psychological, customary, artistic, technical and informational bases. The research also touched on how to magnify linguistic appreciation and its impact on guiding learners towards the learning of human values through literature. It supplies a systematic framework to the prescribed course to identify its strengths and weaknesses with the aim of enhancing its strengths, correcting its weaknesses, and consists of an introduction to the poet, the poem, and the vision of the methodology and is divided into two parts: the first part addresses the lexical level, and the second part addresses the morphological level. The study is expressive and analytical in nature to identify the internal cohesion of the text, deduce its meanings, and direct its implications to noble moral values.